2022
DOI: 10.1002/ptr.7373
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone laxatives use and colorectal cancer: A systematic review and meta‐analysis of observational studies

Abstract: This systematic review and meta‐analysis were conducted to determine the effects of anthraquinone (AQ) laxatives on colorectal cancer (CRC). We searched PubMed, Embase, Google Scholar, and CENTRAL from inception until March 2021, for randomized controlled trials (RCTs) and observational studies. Through the systematic review, we identified 8 observational studies evaluating AQ laxatives use as a risk factor for CRC development, and 5 studies on CRC risk were included in the meta‐analysis using a random‐effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…50 In line with our current study, a recent systematic review on the use of anthraquinone laxatives reported that it is not possible to conclude on the association of anthraquinone laxatives with CRC due to the lack of robust studies; thus, there is a need for high-quality studies to formally test the association of increased risk of CRC with use of stimulant laxatives. 95 …”
Section: Discussionmentioning
confidence: 99%
“…50 In line with our current study, a recent systematic review on the use of anthraquinone laxatives reported that it is not possible to conclude on the association of anthraquinone laxatives with CRC due to the lack of robust studies; thus, there is a need for high-quality studies to formally test the association of increased risk of CRC with use of stimulant laxatives. 95 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study including 718 MC patients and 2,154 healthy people showed that MC is not related to increased diagnosis of colorectal cancer but enhanced polyp detection due to “chromo-endoscopy-like effect” ( Abu Baker et al, 2018 ). A systemic review aiming to determine the effects of anthraquinone laxatives on colorectal cancer has concluded that a history of anthraquinone laxatives use brought an increased trend in colorectal cancer development, although not showing any significance ( Lombardi et al, 2020 ; Lombardi et al, 2022 ). Therefore, medications or therapeutic interventions for MC are required.…”
Section: Melanosis Colimentioning
confidence: 99%
“…These official rhubarbs contain anthraquinones, notably aloe-emodin, rhein, emodin, chrysophanol, and physcion. Anthraquinones are recognized as the most crucial chemical components in the official rhubarbs with several bioactivities such as laxative ( Lombardi et al, 2022 ), anti-inflammation ( Zhang et al, 2020 ), anti-bacterial ( Friedman et al, 2020 ), anti-diabetic ( Arvindekar et al, 2015 ), and anti-cancer properties ( Adnan et al, 2021 ). Most anthraquinones in TCM or herbs exist in the form of glycosides ( Zhao et al, 2014 ; Jintao et al, 2018 ) and plant parts like senna leaves ( Vilanova-Sanchez et al, 2018 ), and Aloe vera ( Hong et al, 2018 ); such plant parts are used to treat constipation ( de Witte, 1993 ).…”
Section: Introductionmentioning
confidence: 99%